Symposium 2: Actor-Network Theory Double-Symposium: Symposium Introduction - Wright, Steve (Proceedings of the International Conference on Networked Learning, 2014)
This double-symposium assembles a group of people, papers and presentations both in the symposium room and connected to it via the Internet. Brought together we will use this time and space to explore the constellation of methods and philosophical approaches that have emerged from the field of science and technology studies as actor-network theory (ANT), material semiotics or the sociology of translation. The symposium comprises a collection of enactments of ANT in relation to prior research and live data from the 2014 conference. Brought together these offer insights for researching, theorising, interfering in and reconfiguring networked learning. ANT’s origins are in ethnographic studies of scientific practices where it was “developed to analyse situations in which it is difficult to separate humans and non-humans, and in which the actors have variable forms and competencies” (Callon, 1998, p. 183). Whilst we have traced origins we have done little thus far to introduce what ANT “is”. That sentence itself poses a challenge, positioning ANT as an it: a singularity. Those familiar with ANT will be well aware of the debates and publications concerned with what ANT is and isn’t (for concise introductions see (Law, 2008; Mol, 2010)) and its intellectual antecedents including Garfinkel’s ethnomethodology and the semiotics of Greimas. We draw attention to Mol’s (2010) term “ANT-tradition” in her account of the sensitive terms and enduring tensions in this enterprise. From here on, we will use the acronym ANT as a convenient shorthand to gesture to the ANT-tradition which Mol articulates thus: the terms “actor”, “network”, “theory”, as well as the terms “order” and “coordination”, will be explored. But mind you, ANT does not define these terms, but rather plays with them. It does not seek coherence. It does not build a stronghold. Instead of crafting an overall scheme that becomes more and more solid as it gets more and more refined, ANT texts are out to move – to generate, to transform, to translate. To enrich. And to betray. (p. 253) This double-symposium offers enactments of ANT and enactments of networked learning in which the inseparability of humans and non-humans are brought to the fore. The symposium is also an experiment, an interfering in what might be regarded as a typical symposium: a collection of papers written around a particular theme. It might be argued that some, perhaps much, work in the ANT-tradition can be regarded as both playful and improvisational in interfering with well-established practices and structures. In this spirit, we seek in this symposium at this conference to place ANT in dialogue with other frameworks in networked learning such as community of Practice Theory (COP) and Cultural Historical Activity Theory (CHAT) and to speak truth to acronyms by representing this as an ANT having a CHAT with a COP. More seriously, how best do we convey something of ANT that is both useful to those unsure of its ideas and useful for people trying to plan their conference schedule? In what follows we first try and give a taste of a little what ANT does as an approach and some of its concerns and interests, then introduce the elements of the symposium where we will materialise the taster - through tasting. If you are reading this then there is a fair chance you submitted a paper for the conference. In doing so you would have encountered the templates for submissions. That document tightly controlled how papers were formatted: the fonts used, margins and spacing and other things that you can do with text and how to format references to other research artefacts. The templates also act to stop you from doing some things, including exactly what we are doing here: using a different font, different margins with a different justification (bad pun intended). ANT explores the ways non-human objects interact with humans and are delegated this kind of power and control: this agency. The template is the conference standards made durable and enforced at a distance. The rules are translated into a different format: rather than just being words and instructions they are now word processor styles and restrictions. Approaches informed by ANT look closely at how these create and affect practices, how assemblages of non-human actors, or “actants” (here: words, templates, formatting rules) come together with human actants in order to flatten such distinctions and enable symmetrical considerations of the way agencies operate to assemble actor-networks and how these become stable or fall apart. ANT is interested in practices, in how they enact different realities: here the conference is enacted as a set of rules for formatting and presenting research through words and standards. In our symposium, ANT is enacted multiply, as is networked learning, as is a symposium. So back to this text which is creating a putative reality (Law, 2012) about a symposium that relies on my writing practices and your reading practices. So why am I writing this in a different format? ANT borrows heavily from its intellectual antecedent ethnomethodology. By breaching this template, by breaking rules that were made absent by a template these are exposed and made present. However, this breaching is done within and by using the methods of the phenomena under study: changing the formatting to show its agency rather than writing about it from a critical position above or outside of this phenomenon. A guiding principle for this symposium has been to ask all the contributors to consider and engage with the medium of dissemination and to consider ways to “speak truth to materials”, a sentiment expressed by Guggenheim (2011) who argues that “much STS continues to work with writing as a single medium ... with regard to the media and translation techniques that scholars use .. to document and display what they have found out, the sociology of translation, as sociology in general is an impoverished science” (p.66). The papers collected here are arguably representations of this impoverishment, however the symposium enables different enactments. We therefore stay true to the original meaning of the word "symposium" from the Greek συμπόσιον coming together to talk, think and drink. What follows is a plan which, as Suchman (1987) powerfully reminds us, is not the way situated actions will be. However we hope it will help those seeking to navigate the conference, though wayfaring may take over once engaged in the symposium.